2003
DOI: 10.1021/bi026952u
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vaccine Development:  Constrained Peptide Immunogens Show Improved Binding to the Anti-HIV-1 gp41 MAb

Abstract: The human immunodeficiency virus type I (HIV-1) transmembrane glycoprotein gp41 mediates viral entry through fusion of the target cellular and viral membranes. A segment of gp41 containing the sequence Glu-Leu-Asp-Lys-Trp-Ala has previously been identified as the epitope of the HIV-1 neutralizing human monoclonal antibody 2F5 (MAb 2F5). The 2F5 epitope is highly conserved among HIV-1 envelope glycoproteins. Antibodies directed at the 2F5 epitope have neutralizing effects on a broad range of laboratory-adapted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 49 publications
(77 reference statements)
2
91
0
Order By: Relevance
“…A more plausible cause is that conformational f lexibility in the oligomannan arms is still high, and the immune response is ''diluted'' by recognition of improper structures within the chemical space. This complicating factor has been proposed as a reason for the inability to mimic the broad neutralizing characteristics of other HIV-1-directed mAbs (4,10,33).…”
Section: 00e+04mentioning
confidence: 99%
See 1 more Smart Citation
“…A more plausible cause is that conformational f lexibility in the oligomannan arms is still high, and the immune response is ''diluted'' by recognition of improper structures within the chemical space. This complicating factor has been proposed as a reason for the inability to mimic the broad neutralizing characteristics of other HIV-1-directed mAbs (4,10,33).…”
Section: 00e+04mentioning
confidence: 99%
“…For several of these mAbs, identification and extensive characterization of the neutralizing epitopes have been realized (4)(5)(6)(7). This structural knowledge has been used to design antigens intended to direct the primary immune response toward the neutralizing epitope (8)(9)(10). However, in all immunization studies performed to date these vaccine candidates have failed to elicit broadly neutralizing antibodies.…”
mentioning
confidence: 99%
“…In addition to simple linear or structurally constrained peptide immunogens, recombinant protein immunogens including displays of constrained 2F5 epitope in the contexts of various protein scaffolds have been also pursued [28][29][30][31][32][33][34][35][36][37]. While inducing high antibody titers against the primary amino acid sequence of the epitope, these immunogens have failed to elicit NAbs against primary HIV-1.…”
Section: Introductionmentioning
confidence: 99%
“…10,20,[23][24][25][26] First, synthetic peptide antigens representing monomeric gp41 peptides are conformationally unstable. Since stability and bioactive conformation are intimately associated with trimeric quaternary structure, they are difficult to duplicate using monomeric peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, attempts to exploit these peptides as immunogens, alone or with additional variable regions, have been unsuccessful. [23][24][25][26] Golding et al 10 and Louis et al 20 showed that antibodies gp41 Protein Mimetics Elicit Neutralizing Antibodies 321 generated against complexed peptides or engineered trimeric peptides based on the N-HR or C-HR domains possess viral neutralizing activity. These results suggest that targeting the bioactive conformations of the N-HR or C-HR domains is a viable vaccine design strategy.…”
Section: Introductionmentioning
confidence: 99%